FAKTOR-FAKTOR YANG MEMPENGARUHI KETIMPANGAN DISTRIBUSI PENDAPATAN DI SULAWESI UTARA - Vredrich Bantika; Olfie L.S. Benu; Gene H.M. Kapantow (COCOS, 2015)
ABSTRACT  This study aimed to analyze whether the population, agricultural land area and economic growth affected the inequality of income distribution in North Sulawesi.  Results of themultiple linear regression analysis gave the coefficient of determination (R2) of 92.3 %.  which included population, land area of agriculture and economic growth as independent variables.  Furthermore, from the three independent variables, only population and economic growth gave significant effect to the Gini Ratio. Judging from the direction of the impact, an increase in economic growth would lower the Gini Ratio, while an increase in the population would also increase the Gini Ratio inNorth Sulawesi. keywords : Income Distribution